Effectiveness of Failure Modes Effect Analysis (FMEA) to Reduce Medical Error - Setiasih, Putri Ingen; Junadi, Purnawan (UI Scholars Hub, 2017)
One of the prevention efforts of medical errors that occur in health services is by identifying the potential failure of the service before the failure occurs. FMEA is one way to identify the risks of failure. Therefore, the authors wanted to find out whether FMEA was effective for reducing medical error based on previous studies. This article was a literature review using references in an online database such as EBSCOhost. The author found 280 articles while searching by using the keyword “FMEA”. After filtered by publication period from 2012 to 2017, full text and language, finally got 7 articles. Finally, the author used the three most relevant literature. FMEA was proven to decrease the potential failure rate after follow-up to failure was done in service process, so medical error can be prevented. In the application of FMEA, bias can occur during the determination of potential failure and determination of scoring on RPN. Therefore, it is expected that the team involved in making FMEA experts in the process of service to be designed. FMEA could prevent medical errors by determining potential failures before failure occurs